Treatment and decolourisation of treated palm oil mill effluent (POME) using oil palm trunk-derived activated carbon as adsorbent. Issue 1 (October 2021) - Lau, K J; Lim, A; Chew, J J; Ngu, L H; Sunarso, J
Abstract: Palm oil mill effluent (POME) has become a serious problem for the oil palm industries because of its high organic contents and other contaminant formation that results in dark colour, turbid and unpleasant odour. In the conventional treatment of POME used in Malaysia, treated POME can still pollute receiving water bodies as colour is one of the major contaminants that is not completely removed. Adsorption is a promising technique for addressing this problem, with a large range of adsorbents to choose from. It works by adhering the pollutants on to the high porous surface area of adsorbent. However, the high cost of coal-based AC that is commonly used can be the limiting factor for its wider application in palm oil industry. Therefore, this work looks into resource recovery (i.e., use of waste stream) from plantation as precursor of AC synthesis to treat its own waste from the palm oil mill. Hence, the suitability of oil palm trunk (OPT) as feedstock for AC application in POME colour removal in the mill is investigated. Experimental run at the as-synthesis OPT-derived AC was performed for validation via POME adsorption test. The result shows that the OPT-derived AC produced can remove the organic pollutants and colour of POME at the dosage of 15% w v −1 within 48 hours.